Performance Analysis of Zakat Institutions Before and During The Covid-19 Pandemic - Khalida Urfiyya; Sulastiningsih, Sulastiningsih (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2022)
The year 2020 was an unexpected year where the world Covid-19 pandemic disrupted both sides of the economy, demand and supply. The massive spread of the virus has proven to affect the decline in economic activity including the tendency to donate. This research uses a quantitative descriptive method that aims to provide an overview and comparison of zakat institutions performance before and during the Covid-19 pandemic. The measurement parameter used is International Standard of Zakat Management (ISZM) which is divided into 2 main variables, efficiency and capacity. The results showed that in general the performance of zakat institutions during the Covid-19 pandemic was quite good and efficient, although there was a decline in donation receipts at LAZ Dompet Dhuafa, but the drop in the number of donations was not lower than the number it received in the year before the pandemic. LAZISNU has the most efficient ratio of program and operational expense, while BAZNAS has the best efficiency level in the ratio of fundraising expense and fundraising efficiency. Furthermore, all zakat institutions have a positive result of working capital ratio, meaning that the zakat institution is still able to cover its operational expenses with the existing balance of amil funds without generating new revenues.